ANALISA MODEL MARS UNTUK PENANGANAN KORUPSI - Rosalita Agustini (Mimbar Administrasi Mandiri, 2024)
This study aims to assess the effectiveness of the Family Planning Program (KB) in the use of contraceptives in the UPTD of the Population Control and Family Planning Office of Caringin Sub-district, Sukabumi District. The KB program has an important role in regulating births, marriage age, and increasing family resilience and welfare. This activity involves married couples and requires the support of husbands. Indonesia's high population growth and geographical issues pose challenges to family planning implementation. The interview results show that by 2023, around 79% of people in Caringin Sub-district will have used contraceptives. This shows an increase in community awareness of the program. However, there are still 21% of the community who have not joined the program. The UPTD of the Population Control and Family Planning Office has the responsibility to provide explanations to those who have not joined the program. In this case, it requires maximum understanding and efficient use of the budget. The family planning program in the use of contraceptives in the UPTD Dinas Pengendalian Penduduk dan Keluarga Berencana Kecamatan Caringin Kabupaten Sukabumi has been running quite well. Public awareness of the program has increased, and the services provided are effective. Coordination with related agencies and directed procedures also play an important role in the success of this program.